2010
DOI: 10.1128/ec.00046-10
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Ume6, a Filament-Specific Transcriptional Regulator, Directs Hyphal Growth via a Pathway Involving Hgc1 Cyclin-Related Protein

Abstract: The ability of Candida albicans, the most common human fungal pathogen, to transition from yeast to hyphae is essential for pathogenicity. While a variety of transcription factors important for filamentation have been identified and characterized, links between transcriptional regulators of C. albicans morphogenesis and molecular mechanisms that drive hyphal growth are not well defined. We have previously observed that constitutive expression of UME6, which encodes a filament-specific transcriptional regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 42 publications
(106 reference statements)
5
53
3
1
Order By: Relevance
“…Genotypes for all strains used in this study are shown in Table 1. The wild-type tetR control strain (PCY87) as well as tetO-UME6 (MBY38) and tetO-UME6 hgc1⌬/⌬ (PCY50) strains were described previously (34,37). In order to construct the tetO-UME6 efg1⌬/⌬ strain (PCY21), primer pairs 1/2 and 3/4 (see Table S1 in the supplemental material for a list of all primers used in this study) were used to generate PCR products corresponding to the 5= and 3= flanking regions (just outside the open reading frame), respectively, of EFG1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotypes for all strains used in this study are shown in Table 1. The wild-type tetR control strain (PCY87) as well as tetO-UME6 (MBY38) and tetO-UME6 hgc1⌬/⌬ (PCY50) strains were described previously (34,37). In order to construct the tetO-UME6 efg1⌬/⌬ strain (PCY21), primer pairs 1/2 and 3/4 (see Table S1 in the supplemental material for a list of all primers used in this study) were used to generate PCR products corresponding to the 5= and 3= flanking regions (just outside the open reading frame), respectively, of EFG1.…”
Section: Methodsmentioning
confidence: 99%
“…Hgc1 is known to form a cyclin/Cdk complex with Cdc28 kinase, which, in turn, is important for septin phosphorylation, inhibition of cell separation, and activation of the Cdc42 master polarity regulator (involved in septin ring organization, vesicle transport to the hyphal tip, and actin polymerization) (38)(39)(40)(41)(42)(43)(44). Expression of UME6 in an hgc1⌬/⌬ mutant strain results in shorter filaments with constrictions at septal junctions (37). Although Hgc1 is directly involved in a variety of mechanisms important for driving C. albicans hyphal growth, a role for Hgc1 in biofilm formation has not yet been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). 19,20 Addition of peptone to nutrient poor WS medium could sequentially decrease filament formation in C. dubliniensis and this was associated with a sequential decrease in UME6 expression (Fig. 1).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Hgc1 is a cyclin of the cyclin-dependent kinase Cdc28 and has an important function in hyphal development, as an hgc1 homozygous deletion mutant is defective in polarized growth and cell chain formation during filamentous growth (652). Hgc1 is also required for proper septa formation, hyphal extension, and agar invasion in filamentation induced by the constitutive expression of the transcriptional regulator UME6 (94). Cdc28 is also involved in morphogenesis, as the depletion of Cdc28 leads to filamentous growth and the expression of hypha-specific transcripts, such as HWP1 and ECE1 (590).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%